2015
DOI: 10.1002/aic.15097
|View full text |Cite
|
Sign up to set email alerts
|

Separation of azeotropic mixtures using air microbubbles generated by fluidic oscillation

Abstract: The feasibility of separating the azeotropic mixture of ethanol-water using microbubble-mediated batch distillation is presented. The effects of the depth of the liquid mixture in the bubble tank and of the inlet air microbubble temperature on the process efficiency were investigated. The enrichment of ethanol in the vapor phase was higher than that achieved at equilibrium conditions for all liquid ethanol mole fractions considered, including the azeotrope. On decreasing the depth of the liquid mixture and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…There are many advantages using the fluidic oscillator in term of cost-effectiveness, robustness, reliability, immobile parts and no requirement of electricity (Zimmerman et al, 2011). The bubbles generated by fluidic oscillation have low energy consumption that distinguish the method from other method such as ultrasonic and rotary disk which require a significant supply energy (Abdulrazzaq et al, 2015). Zimmerman et al, (2008) explained this device acted as a fluidic amplifier with a potential to pinch off hemispherical cap bubble.…”
Section: Seawater and Membrane Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many advantages using the fluidic oscillator in term of cost-effectiveness, robustness, reliability, immobile parts and no requirement of electricity (Zimmerman et al, 2011). The bubbles generated by fluidic oscillation have low energy consumption that distinguish the method from other method such as ultrasonic and rotary disk which require a significant supply energy (Abdulrazzaq et al, 2015). Zimmerman et al, (2008) explained this device acted as a fluidic amplifier with a potential to pinch off hemispherical cap bubble.…”
Section: Seawater and Membrane Sourcesmentioning
confidence: 99%
“…This early break off of bubble formation at the diffuser aperture offers smallest possible bubble size. Fig.2 and Eq.1 illustrates the relationship of the smaller microbubble to have higher surface area to volume ratio which lead to momentum transfer rates, especially for scrubbing the surface of membrane (Abdulrazzaq et al, 2015;Agarwal et al, 2012). A fluidic oscillator mainly consists of 3 parts: one inlet for air supply, two mid ports for the feedback loop, and two exit ports as the oscillation channel outlet.…”
Section: Seawater and Membrane Sourcesmentioning
confidence: 99%
“…Recently, hot microbubble clouds generated by fluidic oscillation in shallow liquids (liquid height approximately a few bubble diameters) were shown to be effective in stripping ethanol from concentrated ethanol–water mixtures (90% (mol/mol) [17] , 50% (mol/mol) [18] and 40% (wt/wt) 19 ) due to high interfacial area for mass transfer, improved mixing in both phases and non-equilibrium mass transfer [17] , [18] , [19] . In our previous work [20] , with a batch stripping system containing dilute ethanol–water mixtures (~4% (v/v)), it was demonstrated that short bubble residence times in the liquid phase are beneficial for ethanol separation, as non-equilibrium mass transfer leads to supersaturated vapour at the point at which the bubbles escape the liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Abdulrazzaq et al [18] describe the strongly non-equilibrium preference for ethanol vaporisation in ethanol-water mixtures by hot microbubble injection. Subsequent modelling by Abdulrazzaq et al [19] clarifies that the non-equilibrium driving force is kinetically much more rapid at vaporising ethanol in all liquid proportions.…”
Section: Introductionmentioning
confidence: 99%